Inflation Expectations in Nepal - Koirala, T. P. (NRB Economic Review, 2008)
There is a significant positive relationship between inflation and inflation expectations in Nepal, where the latter variable has been generated under Adaptive Expectation Hypothesis (AEH). Using 33 annual observations of actual inflation from 1973 to 2006, one percent increase in inflation expectations has 0.83 percent impact on contemporaneous inflation. The forecastability of inflation expectations on current inflation is higher than that of the expected inflation proxied by one-period lagged inflation. The forecastability of the model has been examined on the basis of minimum Root Mean Squared Error (RMSE). Therefore, it is desirable for the policymakers to consider inflation expectations while formulating monetary policy to anchor inflationary expectations of the economic agents.